2016
DOI: 10.1177/1602400309
|View full text |Cite
|
Sign up to set email alerts
|

Distal Femoral Cortical Hypertrophy after Hip Arthroplasty Using a Cementless Double-Tapered Femoral Stem

Abstract: The incidence of DFCH in hips withthe Accolade TMZF stem was 6.2%. Patients with a higher canal flare index and younger age had a higher incidence of DFCH. Nonetheless, DFCH did not affect clinical outcome or femoral stem stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
1
18
2
Order By: Relevance
“…Subsidence was significantly higher (≤ 2 mm) in the presence of CH than in its absence (≤ 1 mm). Our findings contrast with Cho et al [29] who report subsidence to have been lower in hips with CH compared to hips without CH (1.5 versus 3.4 mm). We explain the increased CH in case of subsidence with the primary stability of the Fitmore stem: in case of an optimal press-fit after reaming, the stem has a 3-point fixation (proximal calcar, lateral cortex, medial tip) while if the press-fit was not optimal, the Fitmore stem subsides and locks distally with a 2-point load transfer causing CH.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Subsidence was significantly higher (≤ 2 mm) in the presence of CH than in its absence (≤ 1 mm). Our findings contrast with Cho et al [29] who report subsidence to have been lower in hips with CH compared to hips without CH (1.5 versus 3.4 mm). We explain the increased CH in case of subsidence with the primary stability of the Fitmore stem: in case of an optimal press-fit after reaming, the stem has a 3-point fixation (proximal calcar, lateral cortex, medial tip) while if the press-fit was not optimal, the Fitmore stem subsides and locks distally with a 2-point load transfer causing CH.…”
Section: Discussioncontrasting
confidence: 99%
“…We found that CH affects neither the clinical outcome nor thigh pain, which is in line with other findings [27, 29, 3133].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…According to previous studies, a high canal flare index has been associated with a higher incidence of cortical hypertrophy. 2,30 Although in the current study a great number of patients were classified as Dorr A, thus high canal flare type, there were not statistically more patients scoring Dorr A in the group of patients with cortical hypertrophy compared to those without cortical hypertrophy. Thus, we do not suspect that the Dorr classification A depicts a higher probability of developing cortical hypertrophy in the current study.…”
Section: Discussioncontrasting
confidence: 57%
“…Distal femoral cortical hypertrophy in short-stem THA is an issue often mentioned in the literature. 2,18,[27][28][29][30][31][32][33] The reported incidences are between 0-63% after a minimum 2 years follow-up. Our reported incidence of cortical hypertrophy at 5 years is higher, with 71% of the hips showing cortical hypertrophy with no significant progression over time.…”
Section: Discussionmentioning
confidence: 99%